A group signature based buyer coalition scheme with trustable third party. Issue 17 (2nd September 2017) - Boongasame, Laor; Temdee, Punnarumol; Daneshgar, Farhad
Abstract : Despite the large number of existing buyer coalition schemes and increasing need for trusting relationship in buyer coalitions, no current buyer coalition scheme explicitly addresses trust issues within these schemes in a formalised manner. Without establishing a trusting relationships among various roles, many buyers may not be willing to join the coalitions. This study proposes a solution, in the form of an algorithmic design, as a response to the above need. Specific features of the proposed solution are: (i) the use of 'group signature' in order to guarantees anonymity within a group that results in trustfulness of the relationships and (ii) introducing a new role called 'authority' to maintain and implement anonymity. In addition, the proposed scheme is capable of maintaining 'correctness' and 'accountability' by both identifying misbehaved buyers as well as implementing various punishment methods.Knowledge domain of the study is the common space between three overlapping fields including Electronic Commerce, Communication Technologies and Information Systems.